Association of the MC4R V103I Polymorphism With Obesity: A Chinese Case–control Study and Meta‐analysis in 55,195 Individuals - Du Wang; Jun Ma; Su Zhang; Anke Hinney; Johannes Hebebrand; Yan Wang; Haijun Wang (2009)
Recently, large-scaled studies suggested a negative association of the infrequent allele of the melanocortin-4 receptor (MC4R) V103I polymorphism with obesity. We conducted a Chinese case-control study, meta-analysis in East Asians and in all populations, in order to further assess the association between the V103I polymorphism and reduced body weight and to explore whether the association varies among different ethnic groups. We conducted a case-control study to analyze this polymorphism in 2,012 children of two independent study groups from Beijing, China, no association was found between the V103I polymorphism and obesity or obesity-related phenotypes (P > 0.10). In the meta-analysis of 3,526 individuals from six East Asian studies, I103 carriers had a 31% lower risk for obesity (odds ratio (OR) = 0.69, 95% confidence interval (CI): 0.50-0.94, P = 0.02). Subsequently, we performed a large meta-analysis of the six East Asian studies and 31 studies of other ethnic groups, involving 55,195 individuals with 19,822 obese cases and 35,373 nonobese controls. In total, the individuals with I103 allele had a 21% lower risk for obesity (OR = 0.79, 95% CI: 0.71-0.88, P < 0.0001). In conclusion, this study confirmed and extended the previous findings, suggesting the MC4R V103I polymorphism is negatively associated with human obesity. It provides significant evidence for the association in East Asian populations. Further large-scaled studies in East Asian populations are needed to validate the association.